Technical-Economic Diagnosis and Development Prospects of Quail Farming in Burkina Faso (British Journal of Multidisciplinary and Advanced Studies, 2024)
Poultry farming is a livestock sector that encompasses various bird species, with the most well-known in Burkina Faso being chickens and guinea fowl. These two species receive support from development programs as they significantly contribute to the livelihoods of poor populations. Quails have been recently introduced, presenting technical and economic advantages that could contribute to the development of livestock farming. The study aimed to characterize the profile of stakeholders, conduct a techno-economic diagnosis, and suggest development prospects. Thirty-three farming units were surveyed in the cities of Bobo Dioulasso, Ouagadougou, and Orodara. The socio-demographic aspects of quail farmers, zootechnical aspects of quails, and challenges faced were analyzed.On the socio-economic level, the activity is predominantly practiced by young, educated men, exclusively with secondary and higher education. Zootechnically, the animal productions consist of eggs and meat. Quail production goals prioritize egg production, quail chicks (97%), fattening (76%), and breeder farming (48%).The feeding practices are inadequate, as all farmers (100%) were providing quails with feed intended for laying hens or broilers. Breeding quails reach sexual maturity at 6 weeks, with an average of 250 eggs laid per female and a high hatching rate. Quails also exhibit a high level of hardiness, easily adapting to their environment, and a high level of adaptation to climatic factors (85% of farmers).Quail housing exclusively consists of battery cages. Economically, live quail prices range from 1,500 to 3,000 Fcfa for breeders and consumption quails, and from 2,500 to 4,000 Fcfa for a tray of thirty eggs. Income levels varied from 184,470 to 28,642,945 Fcfa from quail sales. The revealed constraints primarily involve marketing, followed by the issue of inadequate feeding.